2020
DOI: 10.1186/s12957-020-01897-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of enhanced recovery after surgery (ERAS) program in patients undergoing radical prostatectomy: a systematic review and meta-analysis

Abstract: Background: Enhanced recovery after surgery (ERAS) protocol has been identified to be beneficial in the amount of operations such as gastrointestinal surgery. However, the efficacy and safety in robot-assisted laparoscopic prostatectomy/laparoscopic radical prostatectomy (RALP/LRP) still remain controversial. Method: We searched randomized controlled trials and retrospective cohort studies comparing ERAS versus conventional care for prostate cancer patients who have undergone RALP/LRP. ERAS-related data were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Mukkala et al Unplanned visits after radical prostatectomy 9 © 2021 Canadian Urological Association flatulating/defecation time, shorter time to drain removal, while having no effect on re-admission rate or blood loss. 84,85 A meta-analysis from Lv et al showed that ERAS/FTS had a nonsignificant effect on the re-admission rate outcome, hence favoring conventional care. 84 Further tailoring and extension of ERAS/FTS programs, using the synthesis herein, can potentially help for longer-term outcomes, such as UPV.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…Mukkala et al Unplanned visits after radical prostatectomy 9 © 2021 Canadian Urological Association flatulating/defecation time, shorter time to drain removal, while having no effect on re-admission rate or blood loss. 84,85 A meta-analysis from Lv et al showed that ERAS/FTS had a nonsignificant effect on the re-admission rate outcome, hence favoring conventional care. 84 Further tailoring and extension of ERAS/FTS programs, using the synthesis herein, can potentially help for longer-term outcomes, such as UPV.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…The concept of ERAS was first proposed by Dr. Engelman in 1994 (12). In recent years, this multidisciplinary and multimodal perioperative rehabilitation concept has been widely applied in surgeries of various disciplines: colorectal (13), liver (14), gynecological (15), urologic (16), spinal (17), and gastrointestinal surgery (18). Moreover, recent studies have indicated that patients treated with the ERAS program during hepatectomy, laparoscopic colorectal surgery, and spinal surgery have a significant reduction in LOS and risk of postoperative complications (13,14,17).…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of the ERAS protocol in perioperative patient care in operations such as gastrointestinal surgeries have been well defined, its safety and effectiveness in LRP are not yet clear. In a meta-analysis of 784 patients who underwent LRP it was found that the ERAS protocol shortened the LOS [11]. Similarly, in a study of 301 patients who underwent LRP, it significantly reduced the LOS.…”
Section: Discussionmentioning
confidence: 94%